2022
DOI: 10.3390/nu14071334
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Obesity- and Lipid-Related Indices for Predicting Metabolic Syndrome in Chronic Kidney Disease Patients with and without Type 2 Diabetes Mellitus in China

Abstract: Existing obesity- and lipid-related indices are inconsistent with metabolic syndrome (MetS) in chronic kidney disease (CKD) patients. We compared seven indicators, including waist circumference (WC), body mass index (BMI), visceral fat area (VFA), subcutaneous fat area (SFA), visceral adiposity index (VAI), Chinese VAI and lipid accumulation product (LAP), to evaluate their ability to predict MetS in CKD patients with and without Type 2 diabetes mellitus (T2DM) under various criteria. Multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In addition, VAI reflects abdominal fat distribution and dyslipidemia and is associated with insulin resistance (IR), abnormal glucose balance, and an increased risk of cardiovascular disease in adults (43,44). Our previous study in patients with chronic kidney disease found that VAI had a good ability to predict MetS (45), which is consistent with the findings of this study. TYG, a product of TG and FPG, is a new visceral fat assessment tool that is associated with IR (46,47).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, VAI reflects abdominal fat distribution and dyslipidemia and is associated with insulin resistance (IR), abnormal glucose balance, and an increased risk of cardiovascular disease in adults (43,44). Our previous study in patients with chronic kidney disease found that VAI had a good ability to predict MetS (45), which is consistent with the findings of this study. TYG, a product of TG and FPG, is a new visceral fat assessment tool that is associated with IR (46,47).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the study was conducted in the middle-aged and elderly population, whereas our study included people aged 18-79 years. A survey of the Chinese population suggested that VAI outperformed by LAP, WC and BMI as a predictor of metabolic syndrome ( 9 ). Our results show that LAP has the largest AUC (0.7922, 95% CI: 0.7396-0.8447 in men, 0.713, 95% CI: 0.6806-0.7454 in women) and higher predictive value compared to other metrics.…”
Section: Discussionmentioning
confidence: 99%
“…showed that WHtR was better when predicting metabolic syndrome ( 8 ). The value of VAI for diagnosing diabetes has been reported in the literature to be higher than BMI and WC ( 9 ). Another study among Malaysian vegetarians showed that LAP is more strongly related to metabolic syndrome than other indicators ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that WC may better reflect the risk of obesity-associated diseases compared to BMI (37). Li et al found that WC was more effective than BMI in predicting metabolic syndrome in patients with T2DM (38). A prospective cohort study of 11,714 participants suggested that increased WC might result in blood pressure elevation even without increase in BMI (39).…”
Section: Relationship Between Bmi/wc/whtr and Mafld/nafldmentioning
confidence: 99%